PERILAKU BELAJAR MAHASISWA DENGAN PRESTASI AKADEMIK YANG TINGGI DALAM MENGIKUTI PEMBELAJARAN BERBASIS TEKNOLOGI BERDASARKAN PERSPEKTIF SELF-REGULATED LEARNING - Rahmah, Tenriwali Ridha; Setyowibowo, Hari (Jurnal Psikohumanika, 2024)
Technology-based learning requires students' self-regulated learning abilities. This ability should be done because students can take responsibility and control the learning process they go through. Some students experience obstacles in implementing self-regulated learning which ultimately has an impact on academic results and achievements. However, some other students tend to be able to apply self-regulated learning. Therefore, this study aims to determine the application of self-regulated learning to students who have a high academic achievement (GPA) in technology-based learning processes. Participants in this research were students college using a selective sampling. The method used in this research is a mixed-method with an explanatory sequential approach. Data collection techniques used measuring instruments, A-SRL-S, interviews, observations, and document collection. The data obtained will be analyzed quantitatively and qualitatively. The results of this study indicate that students with high academic achievement set specific, challenging, and achievable goals. These goals are made by considering self-efficacy and the results of the task analysis found. From these goals, students also set strategies and self evaluations, where when achieving goals will increase goals but if they are not successful, they will modify the strategies, and seeking assistance if they experience difficulties.